Grading the Nation's Report Card: Research from the Evaluation of NAEP - National Research Council (The National Academies Press, 2000)
The National Assessment of Educational Progress (NAEP), known as the nation's report card, has chronicled students' academic achievement in America for over a quarter of a century. It has been a valued source of information about students' performance, providing the best available trend data on the academic achievement of elementary, middle, and secondary school students in key subject areas. NAEP's prominence and the important need for stable and accurate measures of academic achievement call for evaluation of the program and an analysis of the extent to which its results are reasonable, valid, and informative to the public. This volume of papers considers the use and application of NAEP. It provides technical background to the recently published book, Grading the Nation's Report Card: Evaluating NAEP and Transforming the Assessment of Educational Progress (NRC, 1999), with papers on four key topics: NAEP's assessment development, content validity, design and use, and more broadly, the design of education indicator systems.
Keywords: Education

Starting Out Right: A Guide to Promoting Children's Reading Success - National Research Council (The National Academies Press, 1999)
A devastatingly large number of people in America cannot read as well as they need for success in life. With literacy problems plaguing as many as four in ten children in America, this book discusses how best to help children succeed in reading. This book identifies the most important questions and explores the authoritative answers on the topic of how children can grow into readers, including: What are the key elements all children need in order to become good readers? What can parents and caregivers provide all children so that they are prepared for reading instruction by the time that they get to school? What concepts about language and literacy should be included in beginning reading instruction? How can we prevent reading difficulties starting with infants and into the early grades? What to ask school boards, principals, elected officials, and other policy makers who make decisions regarding early reading instruction. You'll find out how to help youngsters build word recognition, avoid comprehension problems, and more—with checklists of specific accomplishments to be expected at different ages: for very young children, for kindergarten students, and for first, second, and third grade students. Included are 55 activities to do with children to help them become successful readers, a list of recommended children's books, and a guide to CD-ROMs and websites. Great strides have been made recently toward identifying the best ways to teach children to read. Starting Out Right provides a wealth of knowledge based on a summary of extensive research. It is a "must read" for specialists in primary education as well as parents, pediatricians, child care providers, tutors, literacy advocates, policy makers, and teachers.
Keywords: Education

Grading the Nation's Report Card: Evaluating NAEP and Transforming the Assessment of Educational Progress - National Research Council (The National Academies Press, 1999)
Since the late 1960s, the National Assessment of Educational Progress (NAEP)—the nation's report card—has been the only continuing measure of student achievement in key subject areas. Increasingly, educators and policymakers have expected NAEP to serve as a lever for education reform and many other purposes beyond its original role. Grading the Nation's Report Card examines ways NAEP can be strengthened to provide more informative portrayals of student achievement and the school and system factors that influence it. The committee offers specific recommendations and strategies for improving NAEP's effectiveness and utility, including: Linking achievement data to other education indicators. Streamlining data collection and other aspects of its design. Including students with disabilities and English-language learners. Revamping the process by which achievement levels are set. The book explores how to improve NAEP framework documents—which identify knowledge and skills to be assessed—with a clearer eye toward the inferences that will be drawn from the results. What should the nation expect from NAEP? What should NAEP do to meet these expectations? This book provides a blueprint for a new paradigm, important to education policymakers, professors, and students, as well as school administrators and teachers, and education advocates.
Keywords: Education

Improving the Performance of America's Schools (The National Academies Press, 1995)
The purpose of this publication is to sharpen the debate on education by presenting two contrasting statements on school reform—one by Eric Hanushek, summarizing conclusions of a group of economists on the need to revise incentives to improve public school outcomes, the other by Under Secretary of Education Marshall Smith and colleagues at the U.S. Department of Education, presenting the case for standards-based school reform. Neither of these statements represents positions considered and endorsed by the STEP Board or the National Research Council.

Science for All Children: A Guide to Improving Elementary Science Education in Your School District (The National Academies Press, 1997)
Remember the first time you planted a seed and watched it sprout? Or explored how a magnet attracted a nail? If these questions bring back memories of joy and wonder, then you understand the idea behind inquiry-based science—an approach to science education that challenges children to ask questions, solve problems, and develop scientific skills as well as gain knowledge. Inquiry-based science is based on research and experience, both of which confirm that children learn science best when they engage in hands-on science activities rather than read from a textbook. The recent National Science Education Standards prepared by the National Research Council call for a revolution in science education. They stress that the science taught must be based on active inquiry and that science should become a core activity in every grade, starting in kindergarten. This easy-to-read and practical book shows how to bring about the changes recommended in the standards. It provides guidelines for planning and implementing an inquiry-based science program in any school district. The book is divided into three parts. "Building a Foundation for Change," presents a rationale for inquiry-based science and describes how teaching through inquiry supports the way children naturally learn. It concludes with basic guidelines for planning a program. School administrators, teachers, and parents will be especially interested in the second part, "The Nuts and Bolts of Change." This section describes the five building blocks of an elementary science program: Community and administrative support. A developmentally appropriate curriculum. Opportunities for professional development. Materials support. Appropriate assessment tools. Together, these five elements provide a working model of how to implement hands-on science. The third part, "Inquiry-Centered Science in Practice," presents profiles of the successful inquiry-based science programs in districts nationwide. These profiles show how the principles of hands-on science can be adapted to different school settings. If you want to improve the way science is taught in the elementary schools in your community, Science for All Children is an indispensable resource.
Keywords: Education

Undergraduate Education in the Sciences for Students in Agriculture and Natural Resources: Summary of Proceedings of Regional Conferences (The National Academies Press, 1971)
Keywords: Education

Early Experience and Visual Information Processing in Perceptual and Reading Disorders: Proceedings of a Conference Held October 27-30, 1968, at Lake Mohonk, New York, in Association With the Committee on Brain Sciences, Division of Medical Sciences, National Research Council. Edited - National Research Council (The National Academies Press, 1970)
Keywords: Education

Measuring Up: Prototypes for Mathematics Assessment - National Research Council (The National Academies Press, 1993)
Glimpse the future of mathematics assessment in Measuring Up This book features 13 classroom exercises for fourth grade students that demonstrate the dramatic meaning of inquiry, performance, communication, and problem solving as standards for mathematics education. Policymakers, education leaders, classroom teachers, university-based educators, and parents can learn from the use of these genuine mathematics problems to challenge and prepare students for the future. single copy, $10.95; 2-9 copies, $8.50 each; 10 or more copies, $6.95 each (no other discounts apply)
Keywords: Education

Adviser, Teacher, Role Model, Friend: On Being a Mentor to Students in Science and Engineering - Institute of Medicine; National Academy of Sciences; National Academy of Engineering (The National Academies Press, 1997)
This guide offers helpful advice on how teachers, administrators, and career advisers in science and engineering can become better mentors to their students. It starts with the premise that a successful mentor guides students in a variety of ways: by helping them get the most from their educational experience, by introducing them to and making them comfortable with a specific disciplinary culture, and by offering assistance with the search for suitable employment. Other topics covered in the guide include career planning, time management, writing development, and responsible scientific conduct. Also included is a valuable list of bibliographical and Internet resources on mentoring and related topics.
Keywords: Education

Engineering Education: Designing an Adaptive System - National Research Council (The National Academies Press, 1995)
Traditionally, engineering education books describe and reinforce unchanging principles that are basic to the field. However, the dramatic changes in the engineering environment during the last decade demand a paradigm shift from the engineering education community. This revolutionary volume addresses the development of long-term strategies for an engineering education system that will reflect the needs and realities of the United States and the world in the 21st century. The authors discuss the critical challenges facing U.S. engineering education and present a plan addressing these challenges in the context of rapidly changing circumstances, technologies, and demands.
Keywords: Education

Improving America's Schools: The Role of Incentives - National Research Council (The National Academies Press, 1996)
Reform of American education is largely motivated by concerns about our economic competitiveness and American's standard of living. Yet, few if any of the public school reform agendas incorporate economic principles or research findings. Improving America's Schools explores how education and economic research can help produce, in the words of Harvard's Dale W. Jorgenson, "a unified framework for future education reform." This book presents the perspectives of noted experts, including Eric A. Hanushek, author of Making Schools Work, on creating incentives for improved school and student performance; Under Secretary of Education Marshall S. Smith on the Clinton Administration's reform program; and Rebecca Maynard, University of Pennsylvania, on the education of the disadvantaged. This volume explores these areas: The importance of schooling to labor market success. The prospects for combining school-based management with teacher incentives to gain the best of both approaches. The potential of recent innovations in student achievement testing, including new "value-added" indicators. The economic factors involved in maintaining an adequate stock of effective teachers. The volume also explores why, despite similar standards of living, France, the Netherlands, England, Scotland, and the United States produce different levels of education achievement. Improving America's Schools informs the current debate over school reform with a fresh perspective, examples, and data. This readable volume will be of interest to policymakers, researchers, educators, and education administrators as well as economists and employers—it is also readily accessible to concerned parents and the larger community.
Keywords: Education

Learning to Think Spatially - National Research Council (The National Academies Press, 2006)
Learning to Think Spatially examines how spatial thinking might be incorporated into existing standards-based instruction across the school curriculum. Spatial thinking must be recognized as a fundamental part of K–12 education and as an integrator and a facilitator for problem solving across the curriculum. With advances in computing technologies and the increasing availability of geospatial data, spatial thinking will play a significant role in the information-based economy of the twenty-first century. Using appropriately designed support systems tailored to the K–12 context, spatial thinking can be taught formally to all students. A geographic information system (GIS) offers one example of a high-technology support system that can enable students and teachers to practice and apply spatial thinking in many areas of the curriculum.
Keywords: Education

ICT Fluency and High Schools: A Workshop Summary - National Research Council (The National Academies Press, 2006)
Information and communications technology (ICT) pervades virtually all domains of modern life—educational, professional, social, and personal. Yet although there have been numerous calls for linkages that enable ICT competencies acquired in one domain to benefit another, this goal has largely remained unrealized. In particular, while technology skills and applications at work could be greatly enhanced by earlier complementary learning at school—particularly in K-12 education, a formative and influential stage in a person's life—little progress has been made on such linkages. At present, the curricula of most U.S. high schools focus on skills in the use of tools such as specific word-processing software or contemporary Internet search engines. Although these kinds of skills are certainly valuable—at least for a while—they comprise just one component, and the most rudimentary component, of ICT competencies. The National Academies held a workshop in October 2005 to address the specifics of ICT learning during the high school years would require an explicit effort to build on that report. The workshop was designed to extend the work begun in the report Being Fluent with Information Technology, which identified key components of ICT fluency and discussed their implications for undergraduate education. ICT Fluency and High Schools summarizes the workshop, which had three primary objectives: (1) to examine the need for updates to the ICT-fluency framework presented in the 1999 study; (2) to identify and analyze the most promising current efforts to provide in high schools many of the ICT competencies required not only in the workplace but also in people's day-to-day functioning as citizens; and (3) to consider what information or research is needed to inform efforts to help high school students develop ICT fluency.
Keywords: Education

Preventing Reading Difficulties in Young Children - National Research Council (The National Academies Press, 1998)
While most children learn to read fairly well, there remain many young Americans whose futures are imperiled because they do not read well enough to meet the demands of our competitive, technology-driven society. This book explores the problem within the context of social, historical, cultural, and biological factors. Recommendations address the identification of groups of children at risk, effective instruction for the preschool and early grades, effective approaches to dialects and bilingualism, the importance of these findings for the professional development of teachers, and gaps that remain in our understanding of how children learn to read. Implications for parents, teachers, schools, communities, the media, and government at all levels are discussed. The book examines the epidemiology of reading problems and introduces the concepts used by experts in the field. In a clear and readable narrative, word identification, comprehension, and other processes in normal reading development are discussed. Against the background of normal progress, Preventing Reading Difficulties in Young Children examines factors that put children at risk of poor reading. It explores in detail how literacy can be fostered from birth through kindergarten and the primary grades, including evaluation of philosophies, systems, and materials commonly used to teach reading.
Keywords: Education

Resources for Teaching Elementary School Science (The National Academies Press, 1996)
What activities might a teacher use to help children explore the life cycle of butterflies? What does a science teacher need to conduct a "leaf safari" for students? Where can children safely enjoy hands-on experience with life in an estuary? Selecting resources to teach elementary school science can be confusing and difficult, but few decisions have greater impact on the effectiveness of science teaching. Educators will find a wealth of information and expert guidance to meet this need in Resources for Teaching Elementary School Science. A completely revised edition of the best-selling resource guide Science for Children: Resources for Teachers, this new book is an annotated guide to hands-on, inquiry-centered curriculum materials and sources of help in teaching science from kindergarten through sixth grade. (Companion volumes for middle and high school are planned.) The guide annotates about 350 curriculum packages, describing the activities involved and what students learn. Each annotation lists recommended grade levels, accompanying materials and kits or suggested equipment, and ordering information. These 400 entries were reviewed by both educators and scientists to ensure that they are accurate and current and offer students the opportunity to: Ask questions and find their own answers. Experiment productively. Develop patience, persistence, and confidence in their own ability to solve real problems. The entries in the curriculum section are grouped by scientific area—Life Science, Earth Science, Physical Science, and Multidisciplinary and Applied Science—and by type—core materials, supplementary materials, and science activity books. Additionally, a section of references for teachers provides annotated listings of books about science and teaching, directories and guides to science trade books, and magazines that will help teachers enhance their students' science education. Resources for Teaching Elementary School Science also lists by region and state about 600 science centers, museums, and zoos where teachers can take students for interactive science experiences. Annotations highlight almost 300 facilities that make significant efforts to help teachers. Another section describes more than 100 organizations from which teachers can obtain more resources. And a section on publishers and suppliers give names and addresses of sources for materials. The guide will be invaluable to teachers, principals, administrators, teacher trainers, science curriculum specialists, and advocates of hands-on science teaching, and it will be of interest to parent-teacher organizations and parents.
Keywords: Education

Discipline-Based Education Research: Understanding and Improving Learning in Undergraduate Science and Engineering - National Research Council (The National Academies Press, 2012)
The National Science Foundation funded a synthesis study on the status, contributions, and future direction of discipline-based education research (DBER) in physics, biological sciences, geosciences, and chemistry. DBER combines knowledge of teaching and learning with deep knowledge of discipline-specific science content. It describes the discipline-specific difficulties learners face and the specialized intellectual and instructional resources that can facilitate student understanding. Discipline-Based Education Research is based on a 30-month study built on two workshops held in 2008 to explore evidence on promising practices in undergraduate science, technology, engineering, and mathematics (STEM) education. This book asks questions that are essential to advancing DBER and broadening its impact on undergraduate science teaching and learning. The book provides empirical research on undergraduate teaching and learning in the sciences, explores the extent to which this research currently influences undergraduate instruction, and identifies the intellectual and material resources required to further develop DBER. Discipline-Based Education Research provides guidance for future DBER research. In addition, the findings and recommendations of this report may invite, if not assist, post-secondary institutions to increase interest and research activity in DBER and improve its quality and usefulness across all natural science disciples, as well as guide instruction and assessment across natural science courses to improve student learning. The book brings greater focus to issues of student attrition in the natural sciences that are related to the quality of instruction. Discipline-Based Education Research will be of interest to educators, policy makers, researchers, scholars, decision makers in universities, government agencies, curriculum developers, research sponsors, and education advocacy groups.
Keywords: Education

Scientific Research in Education - National Research Council (The National Academies Press, 2002)
Researchers, historians, and philosophers of science have debated the nature of scientific research in education for more than 100 years. Recent enthusiasm for "evidence-based" policy and practice in education—now codified in the federal law that authorizes the bulk of elementary and secondary education programs—have brought a new sense of urgency to understanding the ways in which the basic tenets of science manifest in the study of teaching, learning, and schooling. Scientific Research in Education describes the similarities and differences between scientific inquiry in education and scientific inquiry in other fields and disciplines and provides a number of examples to illustrate these ideas. Its main argument is that all scientific endeavors share a common set of principles, and that each field—including education research—develops a specialization that accounts for the particulars of what is being studied. The book also provides suggestions for how the federal government can best support high-quality scientific research in education.
Keywords: Education

Resources for Teaching Middle School Science - Institute of Medicine; National Academy of Engineering (The National Academies Press, 1998)
With age-appropriate, inquiry-centered curriculum materials and sound teaching practices, middle school science can capture the interest and energy of adolescent students and expand their understanding of the world around them. Resources for Teaching Middle School Science, developed by the National Science Resources Center (NSRC), is a valuable tool for identifying and selecting effective science curriculum materials that will engage students in grades 6 through 8. The volume describes more than 400 curriculum titles that are aligned with the National Science Education Standards. This completely new guide follows on the success of Resources for Teaching Elementary School Science, the first in the NSRC series of annotated guides to hands-on, inquiry-centered curriculum materials and other resources for science teachers. The curriculum materials in the new guide are grouped in five chapters by scientific area—Physical Science, Life Science, Environmental Science, Earth and Space Science, and Multidisciplinary and Applied Science. They are also grouped by type—core materials, supplementary units, and science activity books. Each annotation of curriculum material includes a recommended grade level, a description of the activities involved and of what students can be expected to learn, a list of accompanying materials, a reading level, and ordering information. The curriculum materials included in this book were selected by panels of teachers and scientists using evaluation criteria developed for the guide. The criteria reflect and incorporate goals and principles of the National Science Education Standards. The annotations designate the specific content standards on which these curriculum pieces focus. In addition to the curriculum chapters, the guide contains six chapters of diverse resources that are directly relevant to middle school science. Among these is a chapter on educational software and multimedia programs, chapters on books about science and teaching, directories and guides to science trade books, and periodicals for teachers and students. Another section features institutional resources. One chapter lists about 600 science centers, museums, and zoos where teachers can take middle school students for interactive science experiences. Another chapter describes nearly 140 professional associations and U.S. government agencies that offer resources and assistance. Authoritative, extensive, and thoroughly indexed—and the only guide of its kind—Resources for Teaching Middle School Science will be the most used book on the shelf for science teachers, school administrators, teacher trainers, science curriculum specialists, advocates of hands-on science teaching, and concerned parents.
Keywords: Education

Improving Adult Literacy Instruction: Options for Practice and Research - National Research Council (The National Academies Press, 2012)
A high level of literacy in both print and digital media is required for negotiating most aspects of 21st-century life, including supporting a family, education, health, civic participation, and competitiveness in the global economy. Yet, more than 90 million U.S. adults lack adequate literacy. Furthermore, only 38 percent of U.S. 12th graders are at or above proficient in reading. Improving Adult Literacy Instruction synthesizes the research on literacy and learning to improve literacy instruction in the United States and to recommend a more systemic approach to research, practice, and policy. The book focuses on individuals ages 16 and older who are not in K-12 education. It identifies factors that affect literacy development in adolescence and adulthood in general, and examines their implications for strengthening literacy instruction for this population. It also discusses technologies for learning that can assist with multiple aspects of teaching, assessment,and accommodations for learning. There is inadequate knowledge about effective instructional practices and a need for better assessment and ongoing monitoring of adult students' proficiencies, weaknesses, instructional environments, and progress, which might guide instructional planning. Improving Adult Literacy Instruction recommends a program of research and innovation to validate, identify the boundaries of, and extend current knowledge to improve instruction for adults and adolescents outside school. The book is a valuable resource for curriculum developers, federal agencies such as the Department of Education, administrators, educators, and funding agencies.
Keywords: Education

Knowing What Students Know: The Science and Design of Educational Assessment - National Research Council (The National Academies Press, 2001)
Education is a hot topic. From the stage of presidential debates to tonight's dinner table, it is an issue that most Americans are deeply concerned about. While there are many strategies for improving the educational process, we need a way to find out what works and what doesn't work as well. Educational assessment seeks to determine just how well students are learning and is an integral part of our quest for improved education. The nation is pinning greater expectations on educational assessment than ever before. We look to these assessment tools when documenting whether students and institutions are truly meeting education goals. But we must stop and ask a crucial question: What kind of assessment is most effective? At a time when traditional testing is subject to increasing criticism, research suggests that new, exciting approaches to assessment may be on the horizon. Advances in the sciences of how people learn and how to measure such learning offer the hope of developing new kinds of assessments-assessments that help students succeed in school by making as clear as possible the nature of their accomplishments and the progress of their learning. Knowing What Students Know essentially explains how expanding knowledge in the scientific fields of human learning and educational measurement can form the foundations of an improved approach to assessment. These advances suggest ways that the targets of assessment-what students know and how well they know it-as well as the methods used to make inferences about student learning can be made more valid and instructionally useful. Principles for designing and using these new kinds of assessments are presented, and examples are used to illustrate the principles. Implications for policy, practice, and research are also explored. With the promise of a productive research-based approach to assessment of student learning, Knowing What Students Know will be important to education administrators, assessment designers, teachers and teacher educators, and education advocates.
Keywords: Education